Identity formation of the traditional courtyard shop houses interiors: case study in George Town, Penang - Akram Zwain,; Azizi Bahauddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The traditional Straits Chinese courtyard shop house is the basic building typology of George Town Heritage City for hundreds of years. The shop house is harmonised in its architectural design identity formation. Many studies have shown that the identity formation of traditional Straits Chinese courtyard shop houses underwent a series of transformation throughout the passage of time. Therefore the interiors formation of shop houses buildings have become a threat by losing the authentic identity in George Town Heritage City. Thus, this paper aims to identify the identity formation of the traditional courtyard of shop houses interiors. A qualitative research approach was employed to obtain data from primary and secondary sources. The reason is to understand the design identity of the traditional courtyard architectural components. Thematic analysis was adopted, and five themes were used to present and discussed the results. This study found that the main multi-cultural (Malay, Chinese, and European) has influenced the identity formation of the traditional courtyard shop house interiors. The outcome is a combination of built cultural heritage. Findings also show that focusing on promoting the traditional courtyard identity formation ensures a strong appreciation of its existence. As part of the practical implications, this paper contributes to reawaken policymakers and other stakeholders. This will stir-up the drive for the sustainability of the traditional courtyard shop houses in George Town, Malaysia.